2010
DOI: 10.1158/1541-7786.mcr-09-0473
|View full text |Cite
|
Sign up to set email alerts
|

The Serine Protease HtrA1 Specifically Interacts and Degrades the Tuberous Sclerosis Complex 2 Protein

Abstract: Hamartin and tuberin are products of the tumor suppressor genes TSC1 and TSC2, respectively. Mutations affecting either gene result in the tuberous sclerosis syndrome, a neurologic genetic disorder characterized by the formation of multiple benign tumors or hamartomas. In this study, we report the identification of TSC2, but not TSC1, as a substrate of HtrA1, a member of the human HtrA family proteins of serine proteases. We show the direct interaction and colocalization in the cytoplasm of HtrA1 and TSC2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Further, additional genes were associated with the development of or risk for various neurological disorders, including autism ( ROBO3 53 , SYN3 and GRIK4 68 ), attention deficit hyperactivity disorder ( ISL1 69 ), Tourette’s syndrome ( SLITRK1 70 ), schizophrenia ( NEUROD1 55 and CYFIP1 71 ), and Alzheimer’s disease ( NQO1 72 and FKBP1B 73 ). Several genes on this list, including G2E3 74 , GNAS 75 , and TSC2 76 , are crucial for normal embryonic development. VEGF 77 is important for angiogenesis, a key placental function; CYR61 78 has been implicated in preeclampsia; and two others of the identified genes are involved in trophoblast differentiation and placental development ( PARP1 79 and NEUROD1 80 ).…”
Section: 1 Discussionmentioning
confidence: 99%
“…Further, additional genes were associated with the development of or risk for various neurological disorders, including autism ( ROBO3 53 , SYN3 and GRIK4 68 ), attention deficit hyperactivity disorder ( ISL1 69 ), Tourette’s syndrome ( SLITRK1 70 ), schizophrenia ( NEUROD1 55 and CYFIP1 71 ), and Alzheimer’s disease ( NQO1 72 and FKBP1B 73 ). Several genes on this list, including G2E3 74 , GNAS 75 , and TSC2 76 , are crucial for normal embryonic development. VEGF 77 is important for angiogenesis, a key placental function; CYR61 78 has been implicated in preeclampsia; and two others of the identified genes are involved in trophoblast differentiation and placental development ( PARP1 79 and NEUROD1 80 ).…”
Section: 1 Discussionmentioning
confidence: 99%
“…Results of studies on cancer cell lines and animal models revealed that downregulation of HtrA1 contributed to survival of cancer cells, increased cell migration and metastasis while overexpression of HtrA1 inhibited cell proliferation in vitro and tumor outgrowth in vivo [13e15,28]. It has also been shown that HtrA1 interacts with and degrades tuberin, product of the tumor suppressor TSC2 gene; mutations in this gene are linked to neurologic disorder characterized by formation of multiple benign tumors [29].…”
Section: Human Htra Proteins In Cellular Physiology and Pathogenesismentioning
confidence: 99%
“…Secreted HTRA1 is involved in the homeostasis of the extracellular matrix [9][10][11][12][13][14] , and intracellular HTRA1 localizes to the cytoplasm, microtubules and nucleus 8,15,16 . Microtubule-associated HTRA1 degrades tubulins, thereby inhibiting cell migration 8,17 .…”
mentioning
confidence: 99%